(untitled) (Global Journal of Human-Social Science, 2014)
Chang Chien (1853-1926) was a native of Nant’ung, Kiangsu. In spite of the Various works on Chang Chien, which testify to the significance of his role in modern China, Chang Chien’s Reform ideas is still not well-researched. The purposes of this paper are firstly, to analyze Chang Chien’s Reform ideas systematically and clearly in the hope that it may become a useful reference for researchers on modern Chinese political thought, and secondly, to stimulate scholars for further research. This paper depends more on basic source materials rather than second-hand data. Among various source materials, Chang Chien’s Diary, The Nine Records of Chang Chien and The Complete Work of Chang Chien are the most important. Chang Chien’s Reform ideas may be summarized as follows:1 taking notice of both economic basis and superstructure; 2 elitism; 3 pragmatism; 4 concept of limited change; 5 gradualism; 6 golden means; and 7 government by the people.